Synthesis and biological evaluation of novel 5, 6-dihydropyrimido[4, 5-f]quinazoline derivatives as potent CDK2 inhibitors. Issue 20 (1st November 2018) - Hu, Xiaoxia; Zhao, Hui; Wang, Youzhi; Liu, Zhan; Feng, Bainian; Tang, Chunlei
Graphical abstract: Highlights: New 5, 6-dihydropyrimido[4, 5- f ]quinazoline derivatives were designed and synthesized. CDK2 inhibitory activity was evaluated. Anti-proliferative activity was in vitro evaluated against MCF-7 and HCT116 cells. Molecular docking in the active site of CDK2 enzyme. Abstract: As serine/threonine kinase, the cyclin dependent kinase 2 (CDK2) is a promising target for various diseases such as cerebral hypoxia, cancer, and neurodegenerative diseases. Here we reported the structure-based synthesis and biological evaluation of novel 5, 6-dihydropyrimido[4, 5- f ]quinazoline derivatives as CDK2 inhibitors, which exhibited potent CDK2 inhibitory activities, as well as anticancer activities in low concentration against two human cancer cell lines (MCF-7 and HCT116). In particular, compounds11a and11f (IC50 values of 0.11 and 0.09 μM for CDK2, respectively) have demonstrated significantly inhibitory potency against CDK2 and have showed great inhibitory activities against MCF-7 and HCT116 cell lines.